The Protective Effects of Silkworm (Bombyx mori) Pupae Peptides on UV-Induced Skin Photoaging in Mice - Xiao Lin; Yuting Fan; Liuying Li; Jiamin Chen; Songyuan Huang; Wenqi Yue; Xuli Wu (Foods, 2024)
Silkworm (Bombyx mori) pupae are popular edible insects with high nutritional and therapeutic value. Currently, there is growing interest in the comprehensive application of silkworm pupae. In this study, peptides that exhibited anti-photoaging activity were obtained from silkworm pupae protein, aiming to investigate the protective effects and potential mechanisms of silkworm pupae peptides (SPPs) on skin photoaging. The results showed that SPPs were composed of 900 short peptides and could effectively alleviate skin photoaging progression. They significantly eliminated excessive production of ROS and MDA; meanwhile, they also renovated the antioxidant enzyme activities. The biomarkers related to collagen synthesis and degradation, including hydroxyproline, interstitial collagenase, and gelatinase, demonstrated that SPPs could suppress collagen degradation. Histopathological results showed that SPPs could reduce the inflammatory infiltrate and the thickness of the dermis and epidermis, as well as increase the collagen bundles and muscle fibers. The histopathological and biochemical results confirmed that SPPs could alleviate photoaging by inhibiting abnormal skin changes, reducing oxidative stress, and immune suppression. Overall, these data prove the protective effects of SPPs against the photoaging process, suggesting their potential as an active ingredient in skin photoaging prevention and therapy.